(untitled) (Current Horticulture, 2024)
Different levels of ethyl oleate and potassium carbonate were tried to produce raisins by following DOV method. The application of ethyl oleate and potassium carbonate is found suitable for faster drying of grapes (Vitis virifera L.) in DOV method and able to produce quality raisins. However, application of solution (15 ml ethyl oleate and 25g potassium carbonate in 1L water) on first day and on 4th day (11 ml ethyl oleate and 18 g potassium carbonate in 1L water) was found most effective than other treatments. Further, studies on canopy management, load management and refinement of other agro-techniques are needed to obtain quality raisins by adopting DOV under tropical conditions of India.